Healthcare consumption in congenital heart disease: A temporal life-course perspective following pediatric cases to adulthood - Salma Pardhan; Zacharias Mandalenakis; Kok Wai Giang; Maria Fedchenko; Peter Eriksson; Mikael Dellborg (International Journal of Cardiology Congenital Heart Disease, 2023)
Background: Improvements in diagnosis, intervention, and care of congenital heart disease (CHD) have led to increased survivability and lifelong dependence on healthcare. This study aims to determine the extensiveness of inpatient care episodes across different life-stages and CHD severity compared to matched controls, and to explore how healthcare utilization among pediatric CHD cases have changed over time. Methodology: National registry data was used to conduct a 1:9 matching analysis with age and sex matched controls. Then, Poisson timeseries analysis was used to conduct trend analysis for inpatient healthcare utilization among pediatric cases <18 years of age. Results: Most CHD cases were non-complex (87.3%), with highest hospitalization rates occurring in infancy. Mean number of hospitalizations among complex cases were over twice that of non-complex cases. Also, as age progressed, mean hospitalization for non-complex cases began converging to the control population. In terms of trend analysis within this study period, healthcare utilization increased by 34% among the infant categories, but decreased by 12% and 32% among children between 1-9 years and 10–17 years, respectively. Also, utilization was not trending in one direction substantiating the claim that multiple time periods are required to assess temporal changes within this population. Conclusion: Inpatient healthcare utilization among the CHD population appears to be decreasing over time in most cases, where non-complex cases transitioning to adult care are increasingly converging to the general population. Additionally, this study validates the need to use multiple time-periods when conducting longitudinal studies across the CHD population.